PROBLEMATIKA PELAKSANAAN DIVERSI DALAM PENYIDIKAN PIDANA DENGAN PELAKU ANAK DI KEPOLISIAN RESORT MALANG - Fachrizal Afandi (Arena Hukum)
Abstract Diversion as a new concept in Law 11/2012 on the Juvenile Justice System is becoming problematic in its practices. Several regulations and infrastructures, which obligatoryfor supporting diversionhave not been provideduntil now. This article attempted to see how diversion implementations and its problems during the police investigation.The research has found that the lack of infrastructures and technical regulations on the Law 11/2012 resulted the inefficiency of the diversion implementation. Â